Parental monitoring, parent-adolescent communucation and adolescent sexual risk-taking behaviours - Baloyi, Valeria (My University, 2012)
This study examined the relationship between parental monitoring and parent-adolescent communication, respectively, and sexual risk-taking behaviours. Participants consisted of 197 grade 11 and 12 learners at Bankuna High School and D. Z. J. Mthebule Secondary School in the Greater Tzaneen Municipality. The learners’ ages ranged from 15 years to 25 years. Sexual risk-taking behaviours was determined by assessing adolescents’ use of condoms, and drugs or alcohol, prior to sexual intercourse. The results indicated a statistically significant relationship between parental monitoring and the adolescents’ sexual risk-taking behaviours. However, no association was found between parent-adolescent communication and sexual risk-taking behaviours. Furthermore, the results showed that gender, socio-economic status, family structure and functioning did not play any significant role in the relationship between parental monitoring and parent-adolescent communication respectively, and sexual risk-taking behaviours.
Thesis (M.A. (Clinical Psychology)) -- University of Limpopo, 2012
Keywords: Parenting; Adolescents; Sexual risk-taking behaviours; Parent and teenager; Adolescent psychology; Risk-taking (Psychology) in adolescence; Behavior disorder in adolescence -- Prevention